Ảnh hưởng của sự trải nghiệm đến lòng trung thành của khách hàng: Vai trò trung gian của chất lượng mối quan hệ giữa ngân hàng và khách hàng tại Việt Nam - Phan Chung, Thủy; Phan Thu, Hiền; Trương Thị, Nhi; Nguyễn Lý Kiều, Chinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The purpose of this study is to explore how customer experience influences customer loyalty in Vietnam’s banking sector. By using the PLS-SEM analysis for the survey dataset of 1,080 bank customers, the study shows that customer experience is a high-level, multi-dimensional construct defined by four dimensions, including Bank Image, Front-line Personnel, Moments-of-Truth, and Product and Service Offerings. In addition, our study also shows that customer experience has a positive effect on customer loyalty, and relationship quality between banks and their customers plays a mediating role in this relationship. This research suggests that service providers should not only keep improving customer experience but also building relationship quality to enhance customer loyalty.